Merapi ceria alert: Early childhood education in disaster-prone areas of Mount Merapi - Alan Kusuma; Audia Ananda Saputri; Jihan Ika Ayuningtyas; Dwi Susanti; Fadillah Sandy; Annis Azhar Suryaningtyas (Community Empowerment, 2025)
Dukun Village, Magelang Regency, Central Java, lies within Mount Merapi's eruption-prone zone, necessitating effective disaster preparedness education, especially for vulnerable children. This community service project aimed to provide disaster mitigation education to KB Insan Mulia II children. The project involved preparation, implementation, and evaluation stages. The "Siaga Merapi Ceria" program utilized an interactive approach, including educational games and simulations, actively engaging teachers, students, and parents. Results demonstrate that the program effectively increased KB Insan Mulia II children's understanding of Mount Merapi disaster mitigation, particularly regarding earthquake and eruption scenarios, through engaging educational games and lava experiments. Children's enthusiasm and improved comprehension highlight the program's success.